Computer-supported cognitive mapping for participatory problem structuring. - Kouwen, Frank van; Dieperink, Carel; Schot, Paul P.; Wassen, Martin J (Environment & Planning A, 2009)
A study explored the potential of the Quasta tool, a computer-supported cognitive mapping for participatory problem structuring in decision and planning support. The tool, which enables qualitative analysis of scenarios and simultaneous forecasting and backcasting, was tested in four participatory problem structuring workshops that focused on environmental issues. Findings revealed that this approach enabled stakeholders to be informed about causal relationships, is useful for a qualitative exploration of scenarios, is effective in identifying the need for in-depth knowledge, and has a low threshold for nontechnicians.